Laporan Studi Kelayakan Bisnis Pada Bank Syariah Indonesia KF Malang UNISMA - Dewi, Annisa Sinta; Solekah, Nihayatu Aslamatis (Maliki Interdisciplinary Journal, 2025)
Bank Syariah Indonesia (BSI) Malang UNISMA Functional Office is part of the merger of three state-owned sharia banks which have become the largest sharia banks in Indonesia. This study aims to analyze the business feasibility of BSI KF Malang UNISMA from various aspects, including legal, environmental, market, technical, human resources and financial. The analysis results show that the operations of BSI KF Malang UNISMA have met legal standards, are supported by adequate technology, strategic location, and competent human resources. From a financial aspect, this investment is feasible with a fast Payback Period, positive NPV, and high IRR. BSI has also succeeded in increasing sharia financial literacy through digital services and creating social impact through ZISWAF and creating new jobs. Despite the negative impact on the environment, mitigation measures such as energy efficiency and digitalization have been taken. With broad market potential and a mature business strategy, BSI KF Malang UNISMA has bright prospects to develop as an innovative and highly competitive sharia banking unit